
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.


a: \(=x^5+1-x^5+1=2\)
b: \(=\left(6b^3+2b^2-5b-2\right)\left(3b^2-b+3\right)\)
\(=18b^5-6b^4+18b^3+6b^4-2b^3+6b^2-15b^3+5b^2-15b-6b^2+2b-6\)
\(=18b^5+b^3+5b^2-13b-6\)
c: \(=\left(2a^2+2ab+b^2\right)\cdot2a\left(b^2+2a^2-2ab\right)\)
\(=2a\left[\left(2a^2+b^2\right)^2-4a^2b^2\right]\)
\(=2a\left(4a^4+b^4\right)=8a^5+2ab^4\)

Giải:
\(B=\left(4a^2-4ab+b^2\right)\left(2a+b\right)\)
\(\Leftrightarrow B=\left(2a-b\right)^2\left(2a+b\right)\)
Thay các giá trị của a và b, ta được:
\(B=\left(2.\dfrac{1}{2}-\dfrac{1}{3}\right)^2\left(2.\dfrac{1}{2}+\dfrac{1}{3}\right)\)
\(\Leftrightarrow B=\left(1-\dfrac{1}{3}\right)^2\left(1+\dfrac{1}{3}\right)\)
\(\Leftrightarrow B=\dfrac{4}{9}.\dfrac{4}{3}\)
\(\Leftrightarrow B=\dfrac{16}{27}\)
Vậy ...
B \(=\left[\left(2a\right)^2-2ab+b^2\right]\left(2a+b\right)\)
\(B=\left(2a-b\right)^2\left(2a+b\right)=\left(2a+b\right)\left(2a-b\right)\left(2a-b\right)=\left(4a^2-b^2\right)\left(2a-b\right)\)
Thế a = \(\dfrac{1}{2}\) ; b = \(\dfrac{1}{3}\)ta được:
\(B=\left[4\left(\dfrac{1}{2}\right)^2-\left(\dfrac{1}{3}\right)^2\right]\left(2.\dfrac{1}{2}-\dfrac{1}{3}\right)\)
\(B=\dfrac{16}{27}\)

a) \(a^2+25b^2+17+10b-8a=0\)
\(\Rightarrow a^2-8a+16+25b^2+10b+1=0\)
\(\Rightarrow\left(a-4\right)^2+\left(5b+1\right)^2=0\)
Vì \(\left(a-4\right)^2\ge0\) với mọi a
\(\left(5b+1\right)^2\ge0\) với mọi b
\(\Rightarrow\left(a-4\right)^2+\left(5b+1\right)^2\ge0\) với mọi a,b
Mà \(\left(a-4\right)^2+\left(5b+1\right)^2=0\)
\(\Rightarrow\left\{{}\begin{matrix}\left(a-4\right)^2=0\\\left(5b+1\right)^2=0\end{matrix}\right.\)
\(\Rightarrow\left\{{}\begin{matrix}a-4=0\\5b+1=0\end{matrix}\right.\)
\(\Rightarrow\left\{{}\begin{matrix}a=4\\5b=-1\end{matrix}\right.\)
\(\Rightarrow\left\{{}\begin{matrix}a=4\\b=-\dfrac{1}{5}\end{matrix}\right.\)

a) \(a^4-5a^2+4=\)\(\left(a^4-4a^2\right)-\left(a^2-4\right)=a^2\left(a^2-4\right)-\left(a^2-4\right)=\left(a^2-1\right)\left(a^2-4\right)\)
\(=\left(a-1\right)\left(a+1\right)\left(a-2\right)\left(a+2\right)\)
\(a^4-a^2+4a-4=a^2\left(a^2-1\right)+4\left(a-1\right)=a^2\left(a-1\right)\left(a+1\right)+4\left(a-1\right)\)
\(=\left(a-1\right)\left[a^2\left(a+1\right)+4\right]=\left(a-1\right)\left(a^3+a^2+4\right)\)
\(a^3+a^2+4=\left(a^3+2a^2\right)-\left(a^2+2a\right)+\left(2a+4\right)=a^2\left(a+2\right)-a\left(a+2\right)+2\left(a+2\right)\)
\(=\left(a^2-a+2\right)\left(a+2\right)\)
\(N=\frac{\left(a-1\right)\left(a+1\right)\left(a-2\right)\left(a+2\right)}{\left(a-1\right)\left(a+2\right)\left(a^2-a+2\right)}=\frac{\left(a+1\right)\left(a-2\right)}{a^2-a+2}\)
\(\text{(2a – b)(4a^2 + 2ab +b^2)}\)
= \(\text{2a.4a^2 + 2a.2ab + 2a.b^2 + (-b).4a^2 + (-b).2ab + (-b).b^2}\)
= \(\text{8a^3 + 4a^2b + 2ab^2 – 4a^2b – 2ab^2 – b^3 = 8a^3 – b^3}\)
2a – b)(4a^2 + 2ab +b^2)
= 2a.4a^2 + 2a.2ab + 2a.b^2 + (-b).4a^2 + (-b).2ab + (-b).b^2
= 8a^3 + 4a^2b + 2ab^2 – 4a^2b – 2ab^2 – b^3
= 8a^3 – b^3
\(2a – b)(4a^2 + 2ab +b^2) = 2a.4a^2 + 2a.2ab + 2a.b^2 + (-b).4a^2 + (-b).2ab + (-b).b^2 = 8a^3 + 4a^2b + 2ab^2 – 4a^2b – 2ab^2 – b^3 = 8a^3 – b^3\)